Engineering exosomes for bone defect repair - Ma, Shaoyang; Zhang, Yuchen; Li, Sijia; Li, Ang; Li, Ye; Pei, Dandan (Frontiers in Bioengineering and Biotechnology, 2022)
Currently, bone defect repair is still an intractable clinical problem. Numerous treatments have been performed, but their clinical results are unsatisfactory. As a key element of cell-free therapy, exosome is becoming a promising tool of bone regeneration in recent decades, because of its promoting osteogenesis and osteogenic differentiation function in vivo and in vitro. However, low yield, weak activity, inefficient targeting ability, and unpredictable side effects of natural exosomes have limited the clinical application. To overcome the weakness, various approaches have been applied to produce engineering exosomes by regulating their production and function at present. In this review, we will focus on the engineering exosomes for bone defect repair. By summarizing the exosomal cargos affecting osteogenesis, the strategies of engineering exosomes and properties of exosome-integrated biomaterials, this work will provide novel insights into exploring advanced engineering exosome-based cell-free therapy for bone defect repair.